Role of Interleukin-6 Correlated to C. pneumoniae Infection as a Biomarker for Prediction of Stroke Severity in Young Patients with Acute Ischemic Stroke. (20th July 2014) - Srivastava, M. V. Padma; Bhasin, Ashu; Chaudhry, Rama; Sharma, Sakshi; Vivekanandhan, S.; Bhatia, Rohit; Tripathi, Manjari
Abstract : Background. Stroke in young is the leading cause of morbidity and mortality in the Indian subcontinent with a reported incidence of 15–30% of all stroke patients. The mechanisms for stroke in the young may include unconventional risk factors such as infections. Causative role of C. pneumoniae infection in patients with acute ischemic stroke (AIS) remains unresolved till date, although the link between C. pneumoniae and cerebrovascular disease has been investigated in many studies. This study examined the upregulation of IL-6 after acute cerebral ischemia and correlated the same with the C. pneumoniae antibody titres (IgG, IgA, and IgM). Methods. We studied blood samples from eighty (n = 80 ) acute stroke patients and healthy age- and sex-matched controls. Venous blood samples were drawn within one week from the onset of stroke. Detection of IgA, IgG, and IgM antibodies to C. pneumoniae was done with a validated microimmunofluorescence (MIF) technique from 5 mL of serum in all subjects. Interleukin-6 was estimated with sandwich ELISA method. Results. The IL-6 levels were elevated in patients with a mean 28.9 ± 8.6 pg/mL as compared to 4.7 + 1.8 pg/mL in healthy age-matched controls (95% CI: 37.7 to 78.4;P = 0.004 ). On correlation of IL-6 to stroke severity, it was found that 30 patients with NIHSS between 0 and 15 had mean IL-6 of 24.6 pg/mL and 50 patients had NIHSS of 18.8 (severely affected) with a mean IL-6 of 43.8 pg/mL. On multivariate analysis after adjusting for sex, hypertension, diabetes mellitus, smoking, and alcohol, the IgA seropositivity yielded an adjusted OR for stroke (4.72; 95% CI: 1.61, 13.83;P = 0.005 ), while IgG seropositivity did not show a statistically significant result. We also observed that 81% of cases were seropositive for IgA versus 32% of controls (P = 0.003 ) followed by IgG, as 52.7% of cases were seropositive versus 17.3% of controls (P = 0.05 ). Multiple regression analysis was done with IL-6 as dependent variable to antibody with IL-6 as dependent variable to Cp-IgA, Cp-IgG, and IgM with 10.4% change in the IL-6 titres showing statistical significant resultF (4, 115) = 3.32, P = 0.01 . Conclusions. IL-6 has important role after acute ischemic stroke and is correlated with stroke severity and may correlate to acute or chronic infectious states with C. pneumonia.